Salt-Induced Coil-Globule Transition of Sulfonate-Modified HPAM is Affected by the Branched Chain Length - Wang, Weiming (Langmuir : the ACS journal of surfaces and colloids, 2023)
Polymer flooding is a cheap and efficient method for tertiary oil recovery. However, the failure of partially hydrolyzed polyacrylamide (HPAM) molecules reduces the oil displacement efficiency under high salinity conditions. In this study, we modified HPAM molecules by sulfonic acid groups with different branched chain lengths, and we characterized the structures of these molecules in different salinity solutions through all-atoms molecular dynamics simulation. Compared with the acrylic group, the sulfonate group has excellent salt resistance because of its weak ability to attract cations. When using different lengths of branched linked branch sulfonates, increasing the length of the branched chain can improve the movement ability of sulfonates, so as to play a better salt resistance effect. However, excessive growth of branched chains can cause their association with each other and can lead to polymer folding. Therefore, we believe that the branched chain length of sulfonate should be moderately increased. These results are expected to provide theoretical support for the design and use of salt-resistant polymers